FLUPIRTINE REDUCES MORPHINE REQUIREMENTS AFTER CARCINOMA BREAST SURGERY: A RANDOMIZED DOUBLE BLIND CONTROLLED TRIAL. - ROOPESH JAIN,; BHUPENDRA KUMAR RATRE, (International Journal of Pharma and Bio Sciences, 2013)
Multimodal analgesia is indicated for perioperative pain management to reduce opioid use and its associated adverse effects. NMDA receptor plays an important role in pain mechanism. Activation of K+ channel blocks the NMDA receptor mediated glutamate induced rise in intracellular Ca++ ion. Activation of K+ channel may increase inhibition of nociceptive input and improve pain relief. flupirtine, a selective K+ opener, has demonstrated efficacy in chronic pain conditions such as painful diabetic neuropathy and post-herpetic neuralgia. The objective of the study was to evaluate the efficacy of flupirtine in reducing morphine requirements in patients after carcinoma breast surgery. Fifty patients received either two doses of oral flupirtine 100 mg (2 h before surgery and on first postoperative day) or placebo. All patients received patient-controlled analgesia with morphine for 48 h after operation. Pain and adverse effects were assessed at 0.5, 1, 2, 6, 12, 24, and 48 hrs after surgery on an 11-point numeric rating scale. Twenty-three patients in the flupirtine group and 24 patients in the placebo group completed the study. Morphine requirements during the 48 h after surgery were significantly lower in the flupirtine group [19.5 mg, standard deviation (SD) 14.5 mg] compared with the placebo group (30.3 mg, SD 18.1 mg) (P¼0.017). There were no statistically significant differences between the groups in pain scores (at rest and on movement) or in adverse effects. Perioperative administration of flupirtine reduced postoperative morphine requirements during the first 48 hrs after carcinoma breast surgery, without significant adverse effects.